Hepatic expression of secondary lymphoid chemokine (CCL21) promotes the development of portal-associated lymphoid tissue in chronic inflammatory liver disease. - Grant, A; Goddard, S; Ahmed-Choudhury, J; Reynolds, G; Jackson, D; Briskin, M; Wu, L; Hübscher, S; Adams, D (2002)
The chronic inflammatory liver disease primary sclerosing cholangitis (PSC) is associated with portal inflammation and the development of neolymphoid tissue in the liver. More than 70% of patients with PSC have a history of inflammatory bowel disease and we have previously reported that mucosal addressin cell adhesion molecule-1 is induced on dendritic cells and portal vascular endothelium in PSC. We now show that the lymph node-associated chemokine, CCL21 or secondary lymphoid chemokine, is also strongly up-regulated on CD34(+) vascular endothelium in portal associated lymphoid tissue in PSC. In contrast, CCL21 is absent from LYVE-1(+) lymphatic vessel endothelium. Intrahepatic lymphocytes in PSC include a population of CCR7(+) T cells only half of which express CD45RA and which respond to CCL21 in migration assays. The expression of CCL21 in association with mucosal addressin cell adhesion molecule-1 in portal tracts in PSC may promote the recruitment and retention of CCR7(+) mucosal lymphocytes leading to the establishment of chronic portal inflammation and the expanded portal-associated lymphoid tissue. This study provides further evidence for the existence of portal-associated lymphoid tissue and is the first evidence that ectopic CCL21 is associated with lymphoid neogenesis in human inflammatory disease.